2016
DOI: 10.4028/www.scientific.net/ddf.369.131
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization and Water Sorption in Polyester Matrix Composites Reinforced with Sisal Fiber: An Experimental Investigation

Abstract: In this work we evaluated the mechanical characterization and sorption water of polymer matrix composites reinforced with sisal fibers at different bath temperatures. Experimental tests of tensile (ASTM D 3039), impact (ASTM D 256) and water sorption in samples with rectangular cross section (dimensions of specimens 20x20mm) were made. It was used the unsaturated polyester resin matrix (Resapol 10-316). With the aim of analyzing the tensile strength and the impact, samples were made with fiber content (by weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Water Sorption Kinetics. The analytical results of the average moisture content of the composites under investigation were compared with the experimental data [1] at different temperature and thickness conditions. Figure 3shows this comparison.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Water Sorption Kinetics. The analytical results of the average moisture content of the composites under investigation were compared with the experimental data [1] at different temperature and thickness conditions. Figure 3shows this comparison.…”
Section: Resultsmentioning
confidence: 99%
“…order, for obtain dry mass. Following the fibers were cut in 35 mm lengths [1]. After this procedure the fiber were mixed with the resin (layer by layer) until to fill the mold.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A very interesting aspect that occurred in the literature recently was the fractal dimension and texture analysis of materials [41,42], which showed that the flexural strength of the tested samples had lower values [43].…”
Section: Introductionmentioning
confidence: 99%